KONTESTASI GELAR ADAT â€œSUTTANâ€ DALAM PANGGUNG POLITIK LAMPUNG - Valentina, Annissa (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article examines the shifting of the meaning of the title of adat where thereis a dualism of the function of the title of adat when traditional leaders enter the political world or vice versa, politicians who get customary titles. The highest customary titles such as "Suttan" were only used in Lampung Ethnic traditional ceremonies as indigenous or local because of the sacredness of their meaning, not for all people living in Lampung, but now customary titles are also used by politicians in political contests by attracting attention local people through the procession get titles in traditional ceremonies. The character of Lampung politicians tends to be ethnicistic because many ethnic groups feel excluded by transmigrant communities so they tend to be attracted to politicians who bring local regional issues in campaigning. There is a dualism of meaning caused by the use of customary titles in the campaign of politicians in Lampung Province, manifest titles of custom and controlling people's interest as political masses towards the elite campaign of the indigenous head of the region.